Vliv procvičování na Khan Academy na znalosti a dovednosti žáků v matematice - Vančura, Jiří (Scientia in educatione, 2020)
Two presented quantitative studies examine the effect of online practice on Khan Academy on knowledge and skills of grammar school students. The first study from year 2016/17 focused on the transfer of procedural knowledge acquired online in Khan Academy environment into Czech classroom context. The second study from year 2017/18 investigates the development of conceptual knowledge through online practice or procedural knowledge. Both studies worked with the same sample of 44 students of two same grade classes of a grammar (high) school in Prague. Collected data were subjected to a hypothesis testing with a 5% significance level. The researcher was (at the time of the research) mathematics teacher of the two classes. Whereas the first study arrived at statistically significant and strongly positive results, the second study didn’t show significant development of student’s conceptual knowledge. Secondarily, we investigated a student’s views on the benefits of online practice for their knowledge and skills.